1994
DOI: 10.1172/jci117021
|View full text |Cite
|
Sign up to set email alerts
|

Prejunctional angiotensin II receptors. Facilitation of norepinephrine release in the human forearm.

Abstract: To determine if peripheral angiotensin II (Ang II) prejunctional receptors facilitating NE release exist in humans, we used 13H INE kinetic methodology to measure forearm NE spillover during intrabrachial arterial Ang II infusions in eight normal male subjects. We used the following protocol to optimize conditions for demonstrating these receptors: (a) lower body negative pressure (-15 mmHg) to increase sympathetic nerve activity to skeletal muscle; and (b) intraarterial nitroprusside to maintain a high consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
3

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 44 publications
4
32
3
Order By: Relevance
“…The circulating concentration of Ang II is approximately 5 pmol/l in healthy individuals [51], considerably lower than the concentrations that stimulated insulin secretion in these studies. However, concentrations of locally produced Ang II would be expected to exceed systemic concentrations and may achieve the concentration range used in the current studies, although accurate quantification of tissue concentrations of Ang II is hampered by its short half-life [8,11].…”
Section: Discussioncontrasting
confidence: 59%
“…The circulating concentration of Ang II is approximately 5 pmol/l in healthy individuals [51], considerably lower than the concentrations that stimulated insulin secretion in these studies. However, concentrations of locally produced Ang II would be expected to exceed systemic concentrations and may achieve the concentration range used in the current studies, although accurate quantification of tissue concentrations of Ang II is hampered by its short half-life [8,11].…”
Section: Discussioncontrasting
confidence: 59%
“…In this respect, some authors 2,31 observed that these class compounds are able to enhance the release of noradrenaline by increasing the pre-synaptic Ang II levels and that Ang II-receptor antagonism may facilitate (rather than, as expected, reduce) the sympathetically mediated vasoconstriction in normal subjects. 34 Indeed, in the present investigation we documented a significant increase in noradrenaline levels after irbesartan treatment. On the contrary, no changes in noradrenaline concentrations were observed after trandolapril administration and these results are in agreement with the experimental ones by Raasch et al, 35 who showed that ACE-inhibition increased neuronal uptake of catecholamines in spontaneously hypertensive rats in a blood pressureindependent manner.…”
Section: Discussionsupporting
confidence: 65%
“…These results are in agreement with other studies that also failed to demonstrate enhanced norepinephrine release by angiotensin II during sympathetic activation in humans with and without chronic heart failure, 10 -12 and in particular with Rundqvist et al, 8 who demonstrated that intracoronary administration of the angiotensin-converting enzyme (ACE) inhibitor enalaprilat failed to attenuate the increase in cardiac norepinephrine spillover following sympathetic activation. In contrast, other studies using electrical stimulation in vitro, 1,2,5 as well as studies in humans, 6,7 did demonstrate angiotensin II-induced augmentation of sympathetic activation. Three of these studies were on the heart.…”
Section: Intracoronary Angiotensin II Infusion and Norepinephrine Relmentioning
confidence: 68%
“…There is also evidence, albeit conflicting, that the sympathetic nervous system is activated by the renin-angiotensin system. [1][2][3][4][5][6][7][8][9][10][11][12][13] This activation supposedly occurs through stimulation of angiotensin II receptors within the central nervous system and/or stimulation of presynaptic angiotensin II receptors located at sympathetic nerve terminals. When investigating the sympathetic nervous system and its interaction with the renin-angiotensin system, the heart is of particular interest.…”
mentioning
confidence: 99%